Texture changes during chilled storage of wild and farmed blackspot seabream (Pagellus bogaraveo) fed different diets - Pedro Luis Castro (Wiley, 2021)
Abstract The impact of changes in dietary lipids and protein sources on texture was evaluated on farmed blackspot seabream (Pagellus bogaraveo) throughout 14 days of ice storage and compared with wild fish. A commercial diet formulated with a high proportion of lipids, and two diets formulated with an important reduction of lipid levels by 60% and adding either plant protein sources (LL diet) or fishmeal (LL + diet) were supplied during growth until commercial size was attained. In the wild fish, the raw fillet hardness was significantly higher than in farmed fish during the entire ice‐storage period. In the farmed fish, an increase of muscle lipid accumulation and change of fiber density were responsible for the variations in texture in the raw fillet. The highest reduction was found in fish fed with diets LL+ and LL. The texture parameters studied on the cooked fillets showed no significant differences, neither attributable to the diets nor to the ice‐storage period.